Current Status of Mobile Applications Used in Tourism and Future Projections - Aydoğan, Ayça Nur; Oktay, Kutay (Eurasian Economists Association, 2024)
From past to present, technology continues to develop without stopping and affects every aspect of life. Tourism is one of the sectors where new approaches and new ways of working, brought about by the effects of technology, are being implemented day by day. Many developments such as the invention of the internet, robotics, automatic systems, software and artificial intelligence have affected the tourism sector as well as other sectors. In this study, the current situation of mobile applications, which are a result of the internet and software, in tourism is investigated. In this way, it is aimed to present projections about the use of mobile applications in tourism for the future. Therefore, the study is important in terms of providing a perspective on the future for the tourism sector. The content analysis method, which is within the scope of qualitative research models, was used as a method in the research. In line with this method chosen to achieve the purpose of the research, data was obtained under various criteria. While collecting the data of the research, the top 30 most downloaded tourism mobile applications used in the world via Appstore were discussed. Descriptive information of the applications and the services they offer are presented as research findings.